Efl Students’ Opinions About The Online And Paper-Based Reading Practice in an English Level a1 (cefr) Course Of a Public University In Ecuador - Espol (2017)
This action-research study tried to understand the students’ opinions about the online and paper-based reading practice in english level a1 (cefr) course of a public university in ecuador. In addition, it was intended to explore their reading skills, which involve their reading fluency. Participants of this study were volunteers from two different a1 classes taught by both researchers. The students were asked to read four texts in their digital and hardcopy version and to write a summary. Moreover, the students were part of an interview, observations and had to fulfill a survey. Main findings show that students who read texts in print perceived that their reading skills were better than those when reading digital material. Despite these findings, students were able to read more words in less time by reading digital material due to the tools that are at hand while using this format. Implications of this findings are discussed.